1973
DOI: 10.1073/pnas.70.11.3184
|View full text |Cite
|
Sign up to set email alerts
|

Normal Production of Erythrocytes by Mouse Marrow Continuous for 73 Months

Abstract: Marrow cell transplants from old and young control donors were carried in genetically anemic W/Wv recipients whose anemias were cured by successful transplants. After a maximum of 36 months and four serial transplants, marrow cell lines from both old and younger control donors continued to produce erythrocytes normally. The oldest marrow cell lines had produced erythrocytes normally for 73 months.Normal erythrocyte production was demonstrated by: (1) cure of the anemia in W/WV recipients, (2) normal rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…HSCs reside in the bone marrow in adult mammals and are responsible for blood formation. In early studies, bone marrow cells from young and old mice were found to display similar reconstitution abilities in transplantation assays (Harrison, 1973;Ogden and Micklem, 1976;Harrison et al, 1978). In fact, serial transplantation studies have shown that normal HSCs can sustain blood formation for multiple lifetimes (Harrison, 1979).…”
Section: The Characteristics and Consequences Of Stem Cell Aging Hemamentioning
confidence: 99%
“…HSCs reside in the bone marrow in adult mammals and are responsible for blood formation. In early studies, bone marrow cells from young and old mice were found to display similar reconstitution abilities in transplantation assays (Harrison, 1973;Ogden and Micklem, 1976;Harrison et al, 1978). In fact, serial transplantation studies have shown that normal HSCs can sustain blood formation for multiple lifetimes (Harrison, 1979).…”
Section: The Characteristics and Consequences Of Stem Cell Aging Hemamentioning
confidence: 99%
“…Like all stem cells, hematopoietic stem cells (HSCs) self-renew, and serial transplantation studies show that populations of HSCs can live much longer than the donor from which they were originally isolated. 1 HSCs express telomerase, necessary for chromosome stability during cell division. 2 Together, these observations supported the idea of an immortal HSC.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators find defects in stem cells from old individuals (6)(7)(8), whereas others report no difference in functional abilities of old and young stem cells (9)(10)(11). Recently, Albright and Makinodan (8) suggested that old stem cells cannot multiply as rapidly as can young stem cells immediately after transplantation, although they are able to multiply and differentiate into normally functional immunohemopoietic cells if given adequate time.…”
mentioning
confidence: 99%